Low-spontaneous-explosion body energy-saving series glass and preparation method thereof

By adopting the technology of low self-destructing body energy-saving series of glasses in float glass, the existing float glass has solved the problems of high cost, easy fading, attenuation of heat insulation function and high self-destruction rate in infrared and ultraviolet barriers, and the effects of color uniformity, non-fading, non-attenuation of thermal performance and low self-destruction rate are achieved.

CN119874185APending Publication Date: 2025-04-25XINYI ELECTRONICS GLASS WUHU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411965178.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing float glasses have problems such as high cost, easy fading, attenuation of heat insulation function and high self-destruction rate in terms of infrared barrier and ultraviolet barrier.

Method used

The low self-destructing body energy-saving series of glasses are used, and their compositions include basic components, colorants and rare earth metal oxides. By adjusting the Fe2O3 content and the amount of rare earth metal oxides, T72, T60, and T18 series glasses are prepared to reduce the self-destructing rate and maintain thermal insulation performance.

Benefits of technology

It achieves good color uniformity, no fading, and no attenuation of thermal performance, and reduces the self-destruction rate to one hundred thousand to meet different market demands.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218173900000071
    Figure BDA0005218173900000071
  • Figure BDA0005218173900000081
    Figure BDA0005218173900000081
  • Figure BDA0005218173900000091
    Figure BDA0005218173900000091
Patent Text Reader

Abstract

The invention discloses low-spontaneous-explosion body energy-saving series glass and a preparation method thereof. The low-spontaneous-explosion body energy-saving series glass comprises a basic component, a coloring agent and a rare earth metal oxide, the basic component is prepared from the following components in percentage by mass: 72 to 73 percent of SiO2, 0.5 to 0.7 percent of Al2O3, 0.3 to 1.4 percent of Fe2O3, 8.0 to 9.0 percent of CaO, 3.6 to 3.8 percent of MgO, 13 to 14 percent of Na2O and 0.1 to 0.2 percent of K2O; for T72 series, T60 series and T18 series low-spontaneous-explosion body energy-saving glass, the mass percentages of Fe2O3 in the basic components are respectively 0.5-0.6%, 0.3-0.4% and 1.3-1.4%, and the mass percentages of Fe2O3 in the basic components are respectively 0.5-0.6%, 0.3-0.4% and 1.3-1.4%. The series of the glass are complete, the requirements of different markets can be met, the color uniformity is good, color fading is avoided, the thermal performance is not attenuated, and the spontaneous explosion rate is as low as one hundred thousand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of float glass, and in particular relates to a low self-explosion body energy-saving series glass and a preparation method thereof. Background Art

[0002] Float glass is widely used in various fields due to its excellent performance, such as construction, automobile, electronics, solar energy, etc. In high-rise buildings, float glass has become the preferred material for curtain wall systems due to its good visual effects and sound insulation performance. Float glass has good light transmittance and impact resistance, which can effectively protect the driver's sight and safety. In the automotive field, it is mainly used for the front and rear windshields and side windows of the car. Float glass has the characteristics of high flatness and good light transmittance, which can ensure the image clarity and color reproduction of display devices. In the electronics field, it is mainly used to make screens for display devices such as televisions and computer monitors. In the field of solar energy, float glass can be used to make covers for solar panels to protect solar panels from erosion by the external environment while ensuring the photoelectric conversion efficiency of solar panels.

[0003] In many of the above application scenarios, float glass is required to have a certain ability to block infrared and ultraviolet rays. At present, most of the existing technologies achieve the performance of blocking infrared and ultraviolet rays by deep processing of flat glass, such as: hollow insulation glass, vacuum insulation glass, coated insulation glass, traditional automobile windshield film, etc., such as a production process of hollow tempered glass and hollow tempered glass disclosed in Chinese patent CN118978346 A. The disadvantages of these products are high cost, easy fading over time, weakening of heat insulation function, and easy self-explosion.

[0004] There are a few existing technologies that use body-colored flat glass to achieve thermal insulation performance, but this type of product has high manufacturing costs, difficult to control color uniformity, many bubbles, and low production capacity. For example, CN107935410A discloses a method for body-colored glass. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a low self-explosion body energy-saving series glass and a preparation method thereof. The series is complete and can meet the needs of different markets. It has good color uniformity, does not fade, does not decay in thermal performance, and the self-explosion rate is as low as one in one hundred thousand.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A low self-explosion body energy-saving series glass, the components of which include a basic component, a colorant, and a rare earth metal oxide;

[0008] The components and mass percentages of the basic components are: SiO2 72-73%, Al2O3 0.5-0.7%, Fe2O3 0.3-1.4%, CaO 8.0-9.0%, MgO 3.6-3.8%, Na2O 13-14%, K2O 0.1-0.2%;

[0009] For the T72 series of low self-explosion energy-saving glass, the mass percentage of Fe2O3 in the basic component is 0.5-0.6%; the mass of the colorant and the rare earth metal oxide are 0.0005-0.001% and 0.30-0.40% of the mass of the basic component raw material respectively;

[0010] For the T60 series low self-explosion energy-saving glass, the mass percentage of Fe2O3 in the basic component is 0.3-0.4%; the mass of the colorant and the rare earth metal oxide are 0.0035-0.0045% and 0.30-0.40% of the mass of the basic component raw material respectively;

[0011] For the T18 series low self-explosion energy-saving glass, the mass percentage of Fe2O3 in its basic component is 1.3-1.4%; the mass of the colorant and the rare earth metal oxide are 0.05-0.08% and 0.30-0.40% of the mass of the basic component raw material respectively.

[0012] The colorant is any one or more of CoO, NiO and Se.

[0013] The rare earth metal oxide is a mixture of ytterbium oxide, cerium oxide and antimony tin oxide in a mass ratio of 2.0 to 4.5:1.5 to 2.5:1.

[0014] The present invention also provides a method for preparing the low self-explosion body energy-saving series glass, the method comprising the following steps:

[0015] (1) adding ore raw materials, colorants, and rare earth metal oxides forming the basic components into a kiln for heating and melting, and forming glass liquid after clarification and homogenization;

[0016] (2) The glass liquid flows along the flow channel into the tin bath to be cooled and formed into a glass ribbon;

[0017] (3) Annealing the glass ribbon;

[0018] (4) The annealed glass ribbon is subjected to defect detection, cutting, breaking, surface protection, stacking and packaging to obtain the finished product.

[0019] In the ore raw material, the nickel content of the silica sand is ≤0.5ppm, which can reduce the generation of NiS and reduce the self-explosion rate of the glass.

[0020] For the T72 series low self-explosion energy-saving glass, a reducing agent needs to be added in step (1), and the reducing agent is carbon powder and ferrous oxide.

[0021] The amounts of the carbon powder and ferrous oxide are 0.025-0.030% and 0.16-0.20% respectively of the amount of the ore raw materials forming the basic component.

[0022] In step (1), the top temperature of the kiln is 1595-1605°C, the bottom temperature is 913-923°C, and the clarification temperature is 1475-1485°C; the flow rate of the bubbler during clarification is 8-12 L / min.

[0023] In step (2), the temperature of the glass liquid in the flow channel is 1125-1135°C; the air volume during cooling is 950-1050 Nm 3 / h.

[0024] In step (3), the annealing temperature is 520-550° C., and after annealing, the product is cooled to below 110° C. in the furnace.

[0025] The low self-explosion body energy-saving glass series provided by the present invention consists of basic components, colorants, and rare earth metal oxides. By adjusting the content of Fe2O3 in the basic components and the amount of the colorant, different series of low self-explosion body energy-saving glasses such as T72, T60, and T18 are obtained.

[0026] The low self-explosion body energy-saving series glass provided by the present invention has a small amount of rare earth metal oxide added to the raw materials, and the infrared and ultraviolet absorption effect of rare earth metal ions is utilized to reduce the infrared and ultraviolet direct transmittance. Rare earth ions are the first elements in the periodic table of chemical elements to start filling f orbitals. The 4f electrons of rare earth elements have a complex energy level structure. This is because when the 4f electrons and the surrounding electrons and nuclei undergo Coulomb interaction, Kramer interaction and crystal field effect, the 4f orbital will split, and the energy level difference of the splitting is just located in the ultraviolet, visible and near-infrared regions, making the spectrum of rare earth ions diverse and complex. The atoms or ions of all rare earth elements have an absorption spectrum of about 30,000. Through the regulation of structure and composition, the rare earth ions in the glass can absorb infrared radiation in sunlight, convert the solar radiation energy into the transition of the outer electrons of the rare earth ions, and further dissipate the radiation energy in the glass medium through non-radiative transitions.

[0027] When light waves propagate into a medium, the charges in the medium (such as atomic nuclei and electrons) are affected by an external electric field, causing the charges to shift and polarize. When the frequency of the incident light matches the resonant frequency of the atoms or molecules in the medium, a resonance phenomenon will occur. Near the resonant frequency, the polarization response in the medium is the strongest, causing changes in the absorption, scattering or transmission of light. Rare earth ion doping can be used to make glass produce dielectric polarization resonance. This resonant absorption causes the energy of near-infrared light to be absorbed or scattered by the glass medium instead of propagating to the other side of the medium. By adjusting the type and concentration of rare earth doping, the resonant frequency and intensity of the dielectric polarization resonance can be adjusted, thereby achieving selective absorption or reflection of infrared and ultraviolet light, and achieving the purpose of isolating infrared and ultraviolet radiation.

[0028] When the temperature exceeds 1000°C, NiS in the molten glass will form tiny droplets. When the molten glass is cooled to 797°C, these small droplets crystallize and solidify. At this time, NiS is a high-temperature α-NiS crystal phase (hexagonal system), and its diameter is usually between 0.1 and 0.4 mm, and some are even less than 0.06 mm. When the temperature continues to drop to 379°C, the α-NiS crystal phase will transform into a low-temperature β-NiS (trigonal system), accompanied by a 2.38% volume expansion. When the glass is heated during tempering, the temperature of the inner core of the glass is about 620℃, and all NiS is in the high-temperature α-NiS phase. Then the glass enters the wind grid for rapid cooling, and NiS undergoes a phase change at 379℃. Unlike the production of float glass, the tempering rapid cooling time is very short, and the high-temperature α-NiS phase does not have time to transform into the low-temperature β-NiS, but is "frozen" in the glass as the high-temperature nickel sulfide α phase. Then the subsequent phase change continues at a low speed, and the volume of NiS continues to expand, and its force on the surrounding glass increases accordingly. The tempered glass core itself is a tensile stress layer. When the NiS in the tensile stress layer undergoes a phase change, the volume expansion also forms tensile stress. The two tensile stresses are superimposed together, doubling the stress, which in turn causes the glass to explode. If α-NiS exists in the compressive stress layer on the surface of the glass, even if the glass does not explode, the tempering strength will be significantly reduced.

[0029] In the preparation method of the low self-explosion body energy-saving series glass provided by the present invention, in order to obtain glass with a low self-explosion rate, firstly, high-quality low-nickel ore raw materials are used to effectively control the introduction of nickel; secondly, the conditions for the reaction of nickel and sulfur are reduced. Compared with ordinary glass, a small amount of Fe is added in the present invention. Since the iron content is much greater than Ni, S will react with Fe first, thereby reducing the probability of NiS generation; for T72 series glass, the present invention also effectively reduces the equivalent S content in the glass under strong reducing conditions by adding a strong reducing agent to the raw materials, thereby further reducing the generation of NiS and reducing the self-explosion rate of the glass.

[0030] In order to obtain glass with a high production pass rate, the present invention comprehensively controls the melting, clarification and cooling conditions of the glass during production, improves the glass stripes and increases the glass pass rate.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The low self-explosion main body energy-saving glass provided by the present invention has a complete series, which can meet the needs of different markets, has good color uniformity, does not fade, and has no attenuation of thermal performance.

[0033] 2. Good appearance quality: point defects less than 0.3mm, no scratches, zebra angle ≥50°, glass curvature ≤0.1%, and small deformation in the pulling direction.

[0034] 3. The self-destruction rate is low, as low as one in one hundred thousand.

[0035] 4. The color of the glass can be adjusted by changing the type and amount of colorant. DETAILED DESCRIPTION

[0036] The present invention is described in detail below with reference to the embodiments.

[0037] The nickel content of the silica sand in the ore raw material used in each example is ≤0.5 ppm.

[0038] Example 1

[0039] A low self-explosion body energy-saving T72 series glass, the low self-explosion body energy-saving series glass comprising a basic component, a colorant, and a rare earth metal oxide;

[0040] The components and mass percentages of the basic components are: SiO2 73%, Al2O3 0.6%, Fe2O3 0.5%, CaO 8.9%, MgO 3.8%, Na2O 13%, K2O 0.2%.

[0041] The colorant is CoO; the mass of the colorant is 0.0005% of the mass of the base component raw material.

[0042] The rare earth metal oxide is a mixture of ytterbium oxide, cerium oxide and antimony tin oxide in a mass ratio of 2:2:1; the mass of the rare earth metal oxide is 0.25% of the mass of the basic component raw material.

[0043] The method for preparing the low self-explosion body energy-saving T72 series glass comprises the following steps:

[0044] (1) adding ore raw materials, colorants, rare earth metal oxides and reducing agents which form the basic components into a kiln for heating and melting, wherein the top temperature of the kiln is 1600° C. and the bottom temperature of the kiln is 918° C., and after clarification and homogenization at 1481° C., a glass liquid is formed; the mass of the colorant and the rare earth metal oxide are 0.0005% and 0.25% of the mass of the ore raw materials, respectively; the reducing agents are carbon powder and ferrous oxide; the amounts of the carbon powder and ferrous oxide are 0.0274% and 0.175% of the amount of the ore raw materials, respectively;

[0045] (2) The glass liquid flows along the flow channel into the tin bath and is cooled and formed to obtain a glass ribbon; the temperature of the glass liquid in the flow channel is 1130°C; the air volume during cooling is 1000Nm 3 / h.

[0046] (3) The glass ribbon is annealed at 540°C and then cooled to below 110°C in the furnace;

[0047] (4) The annealed glass ribbon is subjected to defect detection, cutting, breaking, surface protection, stacking and packaging to obtain the finished product.

[0048] Comparative Example 1

[0049] The rest is the same as Example 1, except that the amounts of some raw materials are changed as shown in Table 1. The properties of the glasses prepared in Example 1 and Comparative Example 1 are shown in Table 1.

[0050] Table 1

[0051]

[0052] As can be seen from the table above, with the addition of rare metals and reducing agents, the visible light transmittance decreases linearly, and the ultraviolet and infrared transmittances also decrease linearly. In order to ensure that the visible light transmittance is above 71%, the infrared and ultraviolet transmittances are as low as possible, and considering the cost and process requirements at the same time, the solution of Example 1 is the best solution.

[0053] Example 2

[0054] A low self-explosion body energy-saving T60 series glass, the low self-explosion body energy-saving series glass comprising a basic component, a colorant, and a rare earth metal oxide;

[0055] The components and mass percentages of the basic components are: SiO2 73%, Al2O3 0.5%, Fe2O3 0.4%, CaO 8.2%, MgO 3.8%, Na2O 14%, K2O 0.1%;

[0056] The mass of the colorant and the rare earth metal oxide are 0.0041% and 0.33% of the mass of the basic component raw material respectively;

[0057] The colorants are CoO and Se, and the mass ratio of CoO to Se is 5.83:1.

[0058] The rare earth metal oxide is a mixture of ytterbium oxide, cerium oxide and antimony tin oxide in a mass ratio of 3.6:2:1.

[0059] The method for preparing the low self-explosion body energy-saving T60 series glass comprises the following steps:

[0060] (1) adding ore raw materials, colorants, and rare earth metal oxides forming the basic components into a kiln for heating and melting, with the top temperature of the kiln being 1598° C. and the bottom temperature of the kiln being 915° C., and forming glass liquid after clarification and homogenization at 1485° C.; the mass of the colorant and the rare earth metal oxide are 0.0041% and 0.33% of the mass of the ore raw materials, respectively;

[0061] (2) The glass liquid flows along the flow channel into the tin bath and is cooled and formed to obtain a glass ribbon; the temperature of the glass liquid in the flow channel is 1125°C; the air volume during cooling is 950Nm 3 / h.

[0062] (3) The glass ribbon is annealed at 530°C and then cooled to below 110°C in the furnace;

[0063] (4) The annealed glass ribbon is subjected to defect detection, cutting, breaking, surface protection, stacking and packaging to obtain the finished product.

[0064] Comparative Example 2

[0065] The rest is the same as Example 2, except that the amounts of some raw materials are changed as shown in Table 2. The properties of the glasses prepared in Example 2 and Comparative Example 2 are shown in Table 2.

[0066] Table 2

[0067]

[0068]

[0069] As can be seen from the table above, with the addition of rare metals, the visible light transmittance decreases linearly, and the ultraviolet and infrared transmittances also decrease linearly. In order to ensure that the visible light transmittance is above 63%, the infrared and ultraviolet transmittances are as low as possible, and considering the cost and process requirements at the same time, the solution of Example 2 is the best solution.

[0070] Example 3

[0071] A low self-explosion body energy-saving T18 series glass, the low self-explosion body energy-saving series glass comprising a basic component, a colorant, and a rare earth metal oxide;

[0072] The components and mass percentages of the basic components are: SiO2 72%, Al2O3 0.6%, Fe2O3 1.3%, CaO 9.0%, MgO 3.8%, Na2O 13.2%, K2O 0.1%;

[0073] The mass of the colorant and the rare earth metal oxide are 0.069% and 0.35% of the mass of the basic component raw material respectively.

[0074] The colorants are CoO, NiO and Se, and the mass ratio of CoO, NiO and Se is 13.57:35:1.

[0075] The rare earth metal oxide is a mixture of ytterbium oxide, cerium oxide and antimony tin oxide in a mass ratio of 4:2:1.

[0076] The method for preparing the low self-explosion body energy-saving T18 series glass comprises the following steps:

[0077] (1) adding ore raw materials, colorants, rare earth metal oxides and reducing agents forming the basic components into a kiln for heating and melting, wherein the top temperature of the kiln is 1605° C. and the bottom temperature of the kiln is 923° C., and after clarification and homogenization at 1485° C., a glass liquid is formed; the mass of the colorant and the rare earth metal oxide are 0.069% and 0.35% of the mass of the ore raw materials, respectively;

[0078] (2) The glass liquid flows along the flow channel into the tin bath and is cooled and formed to obtain a glass ribbon; the temperature of the glass liquid in the flow channel is 1135°C; the air volume during cooling is 1050Nm 3 / h.

[0079] (3) The glass ribbon is annealed at 520-550°C and then cooled to below 110°C in the furnace;

[0080] (4) The annealed glass ribbon is subjected to defect detection, cutting, breaking, surface protection, stacking and packaging to obtain the finished product.

[0081] Comparative Example 3

[0082] The rest is the same as Example 3, except that the amounts of some raw materials are changed as shown in Table 3. The properties of the glasses prepared in Example 3 and Comparative Example 3 are shown in Table 3.

[0083] Table 3

[0084]

[0085]

[0086] As can be seen from the table above, with the addition of rare metals, the visible light transmittance decreases linearly, and the ultraviolet and infrared transmittances also decrease linearly. In order to ensure that the visible light transmittance is above 18%, the infrared and ultraviolet transmittances are as low as possible, and considering the cost and process requirements at the same time, the solution in Example 3 is the best solution.

[0087] Comparative Example 4

[0088] The other parts are the same as in Example 1, except that during the preparation, the top temperature of the kiln is 1591°C, the bottom temperature is 929°C, the clarification temperature is 1480°C, the temperature of the glass liquid in the flow channel is 1110°C; the air volume during cooling is 1180Nm 3 / h.

[0089] The glass colors, qualified product rates, self-explosion rates after tempering and application fields produced in the above embodiments and comparative example 4 are shown in Table 4. The tempering conditions (taking 5 mm as an example) are: tempering temperature 680°C, tempering time 1.5 min.

[0090] Table 4

[0091] color Finished product qualification rate / % Self-explosion rate after tempering / % Application Areas Example 1 Teal 95 0.001 Car front, rear and side guards Example 2 Light Gray 94 0.03 Home decoration, building curtain wall, display cabinet Example 3 Dark Gray 93 0.01 Car sunroof Comparative Example 4 green 85 0.3 /

[0092] In Table 4, if there is no damage and it meets the relevant requirements of the ordinary grade of flat glass national quality standard GB11614-2022, the finished product is considered qualified.

[0093] From the above content, it can be seen that the low self-explosion body energy-saving series glass provided by the present invention is complete in series and can meet the needs of different markets. It has good color uniformity, does not fade, and does not attenuate thermal performance.

[0094] The detailed description of a low self-explosion body energy-saving series glass and its preparation method and application with reference to the above-mentioned embodiment is illustrative rather than restrictive. Several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A low self-explosion body energy-saving series glass, characterized in that: The components of the low self-explosion body energy-saving series glass include basic components, colorants, and rare earth metal oxides; The components and mass percentages of the basic components are: SiO2 72-73%, Al2O3 0.5-0.7%, Fe2O3 0.3-1.4%, CaO 8.0-9.0%, MgO 3.6-3.8%, Na2O 13-14%, K2O 0.1-0.2%; For the T72 series of low self-explosion energy-saving glass, the mass percentage of Fe2O3 in the basic component is 0.5-0.6%; the mass of the colorant and the rare earth metal oxide are 0.0005-0.001% and 0.30-0.40% of the mass of the basic component raw material respectively; For the T60 series low self-explosion energy-saving glass, the mass percentage of Fe2O3 in the basic component is 0.3-0.4%; the mass of the colorant and the rare earth metal oxide are 0.0035-0.0045% and 0.30-0.40% of the mass of the basic component raw material respectively; For the T18 series low self-explosion energy-saving glass, the mass percentage of Fe2O3 in its basic component is 1.3-1.4%; the mass of the colorant and the rare earth metal oxide are 0.05-0.08% and 0.30-0.40% of the mass of the basic component raw material respectively.

2. The low self-explosion body energy-saving series glass according to claim 1 is characterized in that: The colorant is any one or more of CoO, NiO and Se.

3. The low self-explosion body energy-saving series glass according to claim 1 or 2, characterized in that: The rare earth metal oxide is a mixture of ytterbium oxide, cerium oxide and antimony tin oxide in a mass ratio of 2.0 to 4.5:1.5 to 2.5:

1.

4. The method for preparing the low self-explosion body energy-saving series glass according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) adding ore raw materials, colorants, and rare earth metal oxides forming the basic components into a kiln for heating and melting, and forming glass liquid after clarification and homogenization; (2) The glass liquid flows along the flow channel into the tin bath to be cooled and formed into a glass ribbon; (3) Annealing the glass ribbon; (4) The annealed glass ribbon is subjected to defect detection, cutting, breaking, surface protection, stacking and packaging to obtain the finished product.

5. The preparation method according to claim 4, characterized in that: In the ore raw material, the nickel content of the silica sand is ≤0.5ppm.

6. The preparation method according to claim 4, characterized in that: For the T72 series low self-explosion energy-saving glass, a reducing agent needs to be added in step (1), and the reducing agent is carbon powder and ferrous oxide.

7. The preparation method according to claim 4, characterized in that: The amounts of the carbon powder and ferrous oxide are 0.025-0.030% and 0.16-0.20% respectively of the amount of the ore raw materials forming the basic component.

8. The preparation method according to claim 4, characterized in that: In step (1), the top temperature of the kiln is 1595-1605°C, the bottom temperature is 913-923°C, and the clarification temperature is 1475-1485°C; the flow rate of the bubbler during clarification is 8-12 L / min.

9. The preparation method according to claim 4, characterized in that: In step (2), the temperature of the glass liquid in the flow channel is 1125-1135°C; the air volume during cooling is 950-1050 Nm 3 / h.

10. The preparation method according to claim 4, characterized in that: In step (3), the annealing temperature is 520-550° C., and after annealing, the product is cooled to below 110° C. in the furnace.

Citation Information

Patent Citations

  • Method for coloring glass body

    CN107935410A

  • Production process of hollow tempered glass and hollow tempered glass

    CN118978346A